SPECIES COMPOSITION AND GEOGRAPHIC DISTRIBUTION OF WEEVIL BEETLES (COLEOPTERA: CURCULIONIDAE) IN THE AGROBIOCENOSE OF MEDIGACO (British Journal of Global Ecology and Sustainable Development, 2024)
It is known that as a result of the rapid growth of the population of Uzbekistan, in order to satisfy the population's demand for food products, it is necessary to implement large-scale measures for the production of these products. This, in turn, requires the development of new lands, the development of science and technology. As a result of the development of new lands, the development of science and technology, the species composition of agrobiocenoses will change. Although representatives of the insect family have been studied in science, in the conditions of Fergana region, Curculionidae and their damage to food production have not been fully studied. Studying weevil beetles and developing measures to combat them is one of the urgent problems of today. In this article, the results of the study on the distribution of weevil beetles and their species composition in medigaco (alfalfa) agrobiocenosis in some districts of Fergana region (Tashloq, Buvayda and Beshariq) are reflected.